2019
DOI: 10.18046/j.estger.2019.153.3202
|View full text |Cite
|
Sign up to set email alerts
|

The influence of open innovation practices on business performance in Mexican family and non-family SMEs

Abstract: Open innovation has emerged as a topic of great importance due to the recognized benefits that it brings to the company's business performance; however, it has been sparsely addressed in SMEs from developing countries. Therefore, this study aims to analyze and discuss the relationship between open innovation and business performance in family and non-family SMEs in Mexico. A survey-based study was carried out on a sample of 308 firms. Following this, the data was analyzed through a structural equation model. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 75 publications
0
2
0
1
Order By: Relevance
“…It is a second qualitative characteristic of the artisan enterprise and does not necessarily qualify it as a family business (González & Córdova, 2020;Li, 2022). Not all smaller firms are family firms (Romero, 2006;García et al, 2019), nor are all family firms smaller (Miller & Le, 2005;Randolph et al, 2019;Ge et al, 2022). Likewise, not all craft enterprises are necessarily family businesses, despite the transmission of craft knowledge within the family nucleus.…”
Section: History Of the Ecuadorian Handicraft Companymentioning
confidence: 99%
“…It is a second qualitative characteristic of the artisan enterprise and does not necessarily qualify it as a family business (González & Córdova, 2020;Li, 2022). Not all smaller firms are family firms (Romero, 2006;García et al, 2019), nor are all family firms smaller (Miller & Le, 2005;Randolph et al, 2019;Ge et al, 2022). Likewise, not all craft enterprises are necessarily family businesses, despite the transmission of craft knowledge within the family nucleus.…”
Section: History Of the Ecuadorian Handicraft Companymentioning
confidence: 99%
“…Lo anterior, contrasta de los mercados amplios donde operan grandes empresas de economías desarrolladas, donde constantemente se exige trabajo colaborativo para innovar y potenciar la capacidad competitiva (García-Vidales et al, 2019;Stanisławskiy, 2020). Esto indica que el trabajo colaborativo en las pymes de las economías emergentes está determinado por la conciencia de los directivos, del rol del entorno, el tamaño del mercado y el contexto donde se desarrolla el mercado.…”
Section: Conclusionesunclassified
“…Considering contingency theory (Daft, 2001;Donaldson, 2001;Lawrence & Lorsch, 1969;Tannenbaum & Schmidt, 1958;von Bertalanffy, 1928von Bertalanffy, /1968), it is observed that organisations are individual, and dependent upon its many influences. Investigating those such influences is popular within the cited business management research (García-Vidales et al, 2019;Venkatesh et al, 2013). This section probes business management literature that considers the multiple influences of the concepts of organisational resilience and open innovation, separately.…”
Section: Influences Of Organisational Resilience and Open Innovationmentioning
confidence: 99%